1/(x+1)(x+2) +1/(x+2)(x+3) +1/(x+3)(x+4)=2019/2020
Nếu 1/3 + 1/6 +1/10 + ...... + 1/x.(x+1) : 2 = 2019/2021
A.x = 2019/2020 B. x = 2019 C. x = 2020 D. x = 2021
x-4/2022+x-3/2021+x-2/2020+x-1/2019=-4
\(\dfrac{x-4}{2022}+\dfrac{x-3}{2021}+\dfrac{x-2}{2020}+\dfrac{x-1}{2019}\text{=}-4\)
\(\dfrac{x-4}{2022}+\dfrac{x-3}{2021}+\dfrac{x-2}{2020}+\dfrac{x-1}{2019}+4\text{=}0\)
\(\left(\dfrac{x-4}{2022}+1\right)+\left(\dfrac{x-3}{2021}+1\right)+\left(\dfrac{x-2}{2020}+1\right)+\left(\dfrac{x-1}{2019}+1\right)\text{=}0\)
\(\dfrac{x-2018}{2022}+\dfrac{x-2018}{2021}+\dfrac{x-2018}{2020}+\dfrac{x-2018}{2019}\text{=}0\)
\(\left(x-2018\right)\left(\dfrac{1}{2022}+\dfrac{1}{2021}+\dfrac{1}{2020}+\dfrac{1}{2019}\right)\text{=}0\)
\(Do:\) \(\dfrac{1}{2022}+\dfrac{1}{2021}+\dfrac{1}{2020}+\dfrac{1}{2019}\ne0\)
\(x-2018\text{=}0\)
\(x\text{=}2018\)
\(Vậy...\)
a) (1 - 1/2) x (1 - 1/3) x (1 - 1/4) x (1 - 1/5) x (1 - 1/6)
b) (1 - 1/2) x (1 - 1/4)x...x (1 - 1/2019) x (1 - 1/2020)
a, \(=\dfrac{1.2.3...5}{2.3...6}=\dfrac{1}{6}\)
X+1/2020+x+2/2019+x+3/2018+x+4/2017+4=0
\(\dfrac{x+1}{2020}+\dfrac{x+2}{2019}+\dfrac{x+3}{2018}+\dfrac{x+4}{2017}+4=0\)
⇔ \(\dfrac{x+1}{2020}+1+\dfrac{x+2}{2019}+1+\dfrac{x+3}{2018}+1+\dfrac{x+4}{2017}+1=0\)
\(\Leftrightarrow\) \(\dfrac{x+2021}{2020}+\dfrac{x+2021}{2019}+\dfrac{x+2021}{2018}+\dfrac{x+2021}{2017}=0\)
⇔ \(\left(x+2021\right)\left(\dfrac{1}{2020}+\dfrac{1}{2019}+\dfrac{1}{2018}+\dfrac{1}{2017}\right)=0\)
\(Do\) \(\left(\dfrac{1}{2020}+\dfrac{1}{2019}+\dfrac{1}{2018}+\dfrac{1}{2017}\right)\ne0\)
⇒ \(x+2021=0\)
⇔ \(x=-2021\)
\(Vậy\) \(x=-2021\)
Tìm x thuộc N biết :
a, ( x- 1 )^3 - 1 = 0
b, ( x - 4 )^2019 = 1
c, ( x - 2019 )^2020 = 0
d, ( x - 1 )^2 = ( x - 1)^3
a) (x - 1)3 - 1 = 0
<=> (x - 1)3 = 0 + 1
<=> (x - 1)3 = 1
<=> (x - 1)3 = 13
<=> x - 1 = 1
<=> x = 1 + 1
<=> x = 2
=> x = 2
b) (x - 4)2019 = 1
<=> (x - 4)2019 = 12019
<=> x - 4 = 1
<=> x = 1 + 4
<=> x = 5
=> x = 5
c) (x - 2019)2020 = 0
<=> (x - 2019)2020 = 02020
<=> x - 2019 = 0
<=> x = 0 + 2019
<=> x = 2019
=> x = 2019
d) (x - 1)2 = (x - 1)3
<=> x2 - 2x + 1 = x3 - 2x2 + x - x2 + 2x - 1
<=> x2 - 2x + 1 = x3 - 3x2 + 3 - 1
<=> x2 - 2x + 1 - x3 + 3x2 - 3 + 1 = 0
<=> 4x2 - 5x + 2 - x3 = 0
<=> (-x2 + 3x - 2)(x - 1) = 0
<=> (x2 - 3x + 2)(x - 1) = 0
<=> (x - 2)(x - 1)(x - 1) = 0
<=> x - 2 = 0 hoặc x - 1 = 0
x = 0 + 2 x = 0 + 1
x = 2 x = 1
=> x = 1 hoặc x = 2
A=[ 2020 x 2019 + 2019 x 2018] x [ 1 + 1/2 : 1 và 1/2 - 1 và 1/3]
\(A=\left(2020\times2019+2019\times2018\right)\times\left(1+\dfrac{1}{2}:1\dfrac{1}{2}-1\dfrac{1}{3}\right)\)
\(A=\left[2019\times\left(2020+2018\right)\right]\times\left(1+\dfrac{1}{2}:\dfrac{3}{2}-\dfrac{4}{3}\right)\)
\(A=4038\times2019\times\left(1+\dfrac{1}{3}-\dfrac{4}{3}\right)\)
\(A=4038\times2019\times0\)
\(A=0\)
x+4/2018+x+3/2019=x+2/2020+x+1/2021
Ta có :\(\frac{x+4}{2018}+\frac{x+3}{2019}=\frac{x+2}{2020}+\frac{x+1}{2021}\)
=> \(\left(\frac{x+4}{2018}+1\right)+\left(\frac{x+3}{2019}+1\right)=\left(\frac{x+2}{2020}+1\right)+\left(\frac{x+1}{2021}+1\right)\)
=> \(\frac{x+2022}{2018}+\frac{x+2022}{2019}=\frac{x+2022}{2020}+\frac{x+2022}{2021}\)
=> \(\frac{x+2022}{2018}+\frac{x+2022}{2019}-\frac{x+2022}{2020}-\frac{x+2022}{2021}=0\)
=> \(\left(x+2022\right)\left(\frac{1}{2018}+\frac{1}{2019}-\frac{1}{2020}-\frac{1}{2021}\right)=0\)
Vì \(\frac{1}{2018}+\frac{1}{2019}-\frac{1}{2020}-\frac{1}{2021}\ne0\)
=> x + 2022 = 0
=> x = -2022
Vậy x = -2022
\(\frac{x+4}{2018}+\frac{x+3}{2019}=\frac{x+2}{2020}+\frac{x+1}{2021}\)
\(\frac{x+4}{2018}+1+\frac{x+3}{2019}+1=\frac{x+2}{2020}+1+\frac{x+1}{2021}+1\)
\(\frac{x+4}{2018}+\frac{2018}{2018}+\frac{x+3}{2019}+\frac{2019}{2019}=\frac{x+2}{2020}+\frac{2020}{2020}+\frac{x+1}{2021}+\frac{2021}{2021}\)
\(\frac{x+2022}{2018}+\frac{x+2022}{2019}=\frac{x+2022}{2020}+\frac{x+2022}{2021}\)
\(\frac{x+2022}{2018}+\frac{x+2022}{2019}-\frac{x+2022}{2020}-\frac{x+2022}{2021}=0\)
\(\left(x+2022\right)\left(\frac{1}{2018}+\frac{1}{2019}-\frac{1}{2020}-\frac{1}{2021}\right)=0\)
\(x+2022=0\left(\frac{1}{2018}+\frac{1}{2019}-\frac{1}{2020}-\frac{1}{2021}\ne0\right)\)
\(x=0-2022\)
\(x=-2022\)
x+1/2020 + x+2/2019 + x+3/2018 + x+4/2017
tìm giá trị nhỏ nhất
A=3(x-4)4
B=5+2(x-2019)2020
C=5+2018(2020-x)2
D=(x-1)2020+(y-x)-1
E=2(x-1)2+3(2x-y)4-2
A=3(x-4)4
Vì (x-4)4 ≥0
=>3(x-4)4 ≥0
Vậy MinA=0
B=5+2(x-2019)2020
Vì (x-2019)2020 ≥0
=>5+(x-2019)2020 ≥5
Để B đạt Min
=>x-2019=0
=>x=2019
Vậy MinB=5 <=>x=2019